Analisis Pengendalian Kualitas Semen di PT X Menggunakan Metode Peta Kendali I-MR - Rani Ayu Sukmawati; Taswati Nova Wijayaningrum (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the quality control of cement at PT X using the Individual Moving Range (I-MR) control chart method. The main question addressed is how to ensure consistent cement quality in light of increasing production demands and resource exploitation. The research positions itself within the manufacturing industry, focusing on statistical quality control methods. Data was collected daily from October 1 to October 31, 2023, with cement quality tested using the Blaine test. The analysis involved creating check sheets and control charts using Minitab 14. The findings indicate that the quality of cement is within statistical control limits, suggesting a stable production process. Key results include the identification of variations in cement quality from different suppliers and the effectiveness of the I-MR method in maintaining product consistency. This study contributes to the improvement of quality control practices in the cement manufacturing industry.